The Antarctic lichen Cetraria subscutata is a synonym of Nephromopsis chlorophylla - Passo, Alfredo; Rodriguez, Juan Manuel; Chiapella, Jorge Oscar; Messuti, Maria Ines (The Lichenologist)
The Parmeliaceae is a highly diverse family among the lichenized Ascomycota, both in terms of species number and morphological and anatomical variation. In recent years molecular phylogenetics have helped to establish a more natural classification. However, there are still some poorly known species. One such case has been the Antarctic species Cetraria subscutata. So far, the species has been collected in Antarctica only four times. As a result, it was never included in the recent molecular studies and is currently considered as an enigmatic species. During the 2014 Argentine Antarctic Survey, we collected specimens of ?C. subscutata? and these were used for phylogenetic studies. The results confirmed that the species does not belong to Cetraria, but to the genus Nephromopsis, and, in fact, it is conspecific with N. chlorophylla (Willd.) Divakar, Crespo & Lumbsch. However, the specimens from Antarctica show some differences with collections from other regions, which are here discussed. Fil: Passo, Alfredo. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Patagonia Norte. Instituto de Investigaciones en Biodiversidad y Medioambiente. Universidad Nacional del Comahue. Centro Regional Universidad Bariloche. Instituto de Investigaciones en Biodiversidad y Medioambiente; Argentina Fil: Rodriguez, Juan Manuel. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Córdoba. Instituto de Investigaciones Biológicas y Tecnológicas. Universidad Nacional de Córdoba. Facultad de Ciencias Exactas, Físicas y Naturales. Instituto de Investigaciones Biológicas y Tecnológicas; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Córdoba. Instituto de Investigaciones Biológicas y Tecnológicas. Universidad Nacional de Córdoba. Facultad de Ciencias Exactas, Físicas y Naturales. Instituto de Investigaciones Biológicas y Tecnológicas; Argentina Fil: Chiapella, Jorge Oscar. ...